Estudo da remoção de contaminantes emergentes em estação de tratamento de esgoto equipada com biorreator acoplado a filtração por membrana: uma alternativa para a produção de água de reuso - Machado, Rafaela Gonçalves (2022)
The degradation of water bodies and the indiscriminate use associated with frequent and intense drought episodes have compromised the availability of water. Thus, the production of reused water from sewage treatment has been a highly encouraged practice. However, the concern with water resources is not restricted to availability, but also to water quality. In this sense, emerging contaminants in aquatic matrices have attracted the attention of researchers, since the effect of long-term exposure on aquatic ecosystems and human health is not yet fully known, and considering the fact that sewage treatment plants (ETE) represent the main source of emission of these pollutants in receiving bodies, it is important to understand the occurrence and dynamics of these pollutants in ETE, in order to reveal compounds that can be used as chemical markers of treatment efficiency. Thus, the present study was carried out and evaluated the occurrence, spatio-temporal distribution, and removal of emerging contaminants in a Reuse Water Production Station - EPAR Capivari II (Campinas-SP) equipped with a bioreactor coupled to a water filtration membrane (MBR). In a second moment, surface water was collected from rivers in the interior of the State of Sao Paulo, for later comparison (in terms of emerging contaminants concentration) with the reuse water produced by EPAR. The investigated compounds were determined by liquid chromatography coupled to mass spectrometry (UPLC-MS/MS) and by gas chromatography coupled to mass spectrometry (GC-MS). The compounds studied were detected in all samples of raw sewage from the sampling campaigns, with caffeine being the compound found in the highest concentrations, whose range varied from 14379 to 131358 ng/L, with a median equal to 56709 ng/L. Regarding removal, the contaminants with the highest mean values were paracetamol (≅100.0%), caffeine (99.8%), ibuprofen (99.2%) and its metabolites, 1-hydroxy-ibuprofen (≅100.0%) and 2-hydroxy-ibuprofen (96.7%), naproxen (97.8%) and atenolol (97.5%). Among the compounds that showed moderate removal are diclofenac and propranolol with removals of 70.5% and 61.5%, respectively. The estrogenic compounds showed removals of 88.0% for 17-β-estradiol, 33.6% for estrone and 33.0% for 17-α-ethinylestradiol. On the other hand, carbamazepine and its metabolites (10,11-dihydro-10,11-dihydroxy-carbamazepine and 2-hydroxy-carbamazepine) showed a persistent behavior during sewage treatment. Carbamazepine obtained the removal of -7.36% and due to several factors that justify its persistence during sewage treatment, it was possible to point it out as a chemical marker of treatment efficiency. In view of the comparison of reuse water produced by EPAR and water from springs, it was concluded that it is necessary to use complementary treatments for the removal of emerging contaminants when the use of this water requires a more restrictive quality standard in relation to this parameter. However, the reuse water produced by the MBR system has good quality in terms of caffeine removal, total organic load, total suspended solids, turbidity, coliforms, among other parameters.